Insect pests of beans in Africa: Their ecology and management - Abate, T.; Ampofo, James Kwasi O. (Annual Reviews, 1996)
Damage by insect pests, inter alia, is considered the liming factor of bean production in Africa. This paper reviews the current status of insect pests of beans, focusing on their ecology and management, as well as the potential for integrated pest management (IPM) approaches in subsistence fanning conditions, under which most beans are grown in Africa. Although numerous insect pests attack all parts of beans, bean stem maggots and bruchids are the most important field and storage pests, respectively. Foliage beetles, flower thrips, pollen beetles, pod borers, pod bugs, and sap suckers such as aphids also inflict signifcant damage. Control of bean pests in Africa is achieved through the use of a traditional IPM approach that consists of appropriate sowing dates, optimum plant density, varietal mixtures, intercropping, good crop husbandry, and locally available materials. Research should focus on low-input IPM approaches that encompass fanners' current practices, host-plant resistance, and natural biological control.